Correlation and optimal cut-off determination of waist-hip circumference and ratio among health science students - Khadka, Sitaram; Amgain, Kapil; Subedi, Prativa; Kumar Yadav, Gopal; Prasad Gupta, Ravi; Lamichhane, Sabitri; Abdul Jabar Adnan, Muhammad (Journal of Chitwan Medical College, 2025)
Introduction: Body mass index (BMI), waist circumference (WC), hip circumference (HC), and waist-hip ratio (WHR) are commonly used anthropometric indices to define obesity. This study aims to find the correlation between anthropometric parameters and corresponding cut-off point of WC, HC, and WHR related to BMI. Method: A cross-sectional study was conducted among undergraduate students in Punjab University College of Pharmacy, Pakistan, from Jan to Jun 2021. The cut-off of WC, HC, and WHR with BMI (for obese ≥25 kg/m2 for Asia-Pacific population) was calculated using the receiver operating characteristic curve (ROC). Ethics approval was obtained. A sample size was calculated using Cochrane’s formula. Normality of data distribution was checked. Pearson correlation coefficient was applied for correlation between variables like BMI, WC, HC, weight, height, and WHR at a 95% confidence interval. The ROC analyses were used for reliability of WC, HC, and WHR with high BMI. Result: Out of 433 participants, correlation coefficients between BMI and WC, BMI and HC, BMI and WHR, and HC and WC were 0.583 (p<0.001), 0.518 (p<0.001), 0.156 (p<0.001), and 0.743 (p<0.001). For BMI 25 kg/m2, the optimal cut-off points for WC, HC, and WHR were 82.55 cm, 95.25 cm, and 84 cm. Conclusion: There was a positive linear correlation of BMI with WC, HC, and WHR, and also between WC and HC. The optimal cut-off points for WC, HC, and WHR corresponding to a BMI of 25 kg/m2 were less than the WHO standard cut-off point.